PENGARUH MINAT BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS KELAS VII DI SMP NEGERI 1 BESUKI SEMESTER GENAP - Ahmad Hafas Rasyidi; Minarsi Minarsi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
Someone who has an interest in certain activities tends to pay great attention to these activities. Of course, in carrying out activities and efforts to achieve goals, there is a need for an impetus to foster the interest carried out by teachers, the enthusiasm of educators in teaching students is closely related to the interests of students who are learning. to determine the effect of interest in learning on student learning outcomes in class VII social studies subjects at SMP Negeri 1 Besuki even semester of the 2017/2018 school year. In this study, using the method of determining research respondents using proportional randem sampling, which only took half of the number of class VII respondents at SMP Negeri 1 Besuki even semester of the 2017/2018 school year. From the results of the calculation of the analysis of variance of the regression line, it is obtained Freg of 164.2353. And if you consult the F table for db = 2 and db = 51 with a significant level of 5% obtained 3.1650. Thus the results of these calculations show that Freg is greater than the F-table which means that the interest in learning is significant towards learning outcomes. for the results of the first minor analysis for the significant test between internal learning interest and student learning outcomes, the F-count results are 164.2353 and a significant level of 5%. For the results of the second minor analysis to test the significant interest in internal learning on student learning outcomes obtained results F-count 164.2353 and a significant level of 5%. Furthermore, the effectiveness of the regression line was obtained at 87.2462%. This means that the effective contribution of the overall predictors of student learning outcomes contributed 87.2462%. while other predictors that were not studied gave 38.95%. The effective contribution (SE) of the doctor (X1) of interest in internal learning is 70.1411% towards the criterion (Y) of student learning outcomes. The effective contribution (SE) predictor (X2) of interest in external learning is 17.1051% towards the criterion (Y) of student learning outcomes.